Dialogue with the other. - Isaak, Jo Anna (Odense : Kunsthalle Brandts Klaedefabrik, 1994)
Abramovic, Marina ; Barmen, Bianca Maria ; Bourgeois, Louise ; Burki, Marie José ; Chadwick, Helen ; Chunn, Nancy ; Cross, Dorothy ; Dumas, Marlene ; Fleury, Sylvie ; Francken, Ruth ; Hicks, Nicola ; Holzer, Jenny ; Jelstrup, Dorte ; Justesen, Kirsten ; Klein, Astrid ; Lassnig, Maria ; Navares, Paloma ; Nakhova, Irina ; Nyborg, Hege ; Oppermann, Anna ; Ortwed, Kirsten ; Rist, Pipilotti ; Sherman, Cindy ; Sieverding, Katharina ; Simotova, Adriena ; Smith, Kiki ; Spero, Nancy ; Steir, Pat ; Trockel, Rosemarie ; Uutinen, Marianna
Dialogue with the other, Kunsthalle Brandts Klaedefabrik, Odense, June 18 - September 10, 1994
boek